Geoestratégia do desenvolvimento recente da China:a interiorização do crescimento - Aniel Lima dos Santos (Confins)
The Chinese model has its geographical expression, produced, among other factors, by territorial policies applied starting from the policy of "Reform and Opening", but also influenced by the history of China’s territorial formation; a certain vision of the development already appears in littoral China, and the Chines authorities now try to promote it inside the territory, a phenomenon which we will seek to analyze in this paper.